NUMERICAL SIMULATION OF THE PERFORMANCE OF A CFD-BASED SAVONIUS-DARRIEUS HYBRID WIND TURBINE WITH VARIATIONS IN COUPLING ANGLE AND WIND SPEED AT RR 0.28 - Argyono Cahyono Adi; Alviani Hesthi Permata Ningtyas (Trends in Mechanical Engineering Research, 2026)
This study aims to evaluate the aerodynamic characteristics of a Savonius-Darrieus hybrid wind turbine through a numerical simulation approach based on Computational Fluid Dynamics (CFD). Numerical analysis was carried out using ANSYS Fluent 2023 R1 software to examine the effect of changing the coupling angle by 0˚, 30˚, and 60˚ at wind speeds of 2.5 m/s and 3.5 m/s. Turbine performance evaluation was also carried out at several Tip Speed Ratio (TSR) values, namely 0.81; 1.3; and 2. The parameters observed in this study include the power coefficient (Cp), moment coefficient (Cm), torque characteristics, turbine output power, and efficiency. The results showed that the coupling angle configuration has a significant effect on the aerodynamic behavior and energy conversion capability of the hybrid turbine. Of all tested configurations, the highest Cp value of 0.042 and turbine efficiency of 4.2% were obtained at a wind speed of 3.5 m/s with coupling angles of 30° and 60° at a TSR of 1.3, resulting in an output power of 0.441 W. In addition, the turbine exhibited stable rotational characteristics and improved self-starting capability at low wind speeds. These findings indicate that the Savonius–Darrieus hybrid turbine has promising potential for small-scale renewable energy applications, particularly in low to moderate wind speed environments commonly found in urban and coastal areas. This study also confirmed that the hybrid configuration is able to improve the stability and overall performance of the turbine compared to a conventional vertical axis turbine operating under similar environmental conditions.